Penanaman Bibit Pucuk Merah (Syzygium oleina) Sebagai Upaya Menjaga Lingkungan Hidup Di Sekolah Dasar Negeri Cibodas 1, Desa Cibodas - Putra, Teguh; Ferdiana, Fadlan; Akbar, Eka; Rahmasari, Lina Kamila (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
The activity of planting red shoots (Syzygium oleina) at Cibodas 1 Elementary School is one of the efforts to revitalize the environment and educate students about the importance of preserving nature. This activity is carried out with the primary goal of improving the quality of the school environment through greening and instilling environmental values in students from an early age. The implementation methods include selecting the planting location, providing environmental education materials to students, and directly involving students in planting red shoot seedlings with guidance from teachers and the implementation team. Red shoot trees were chosen due to their ability to absorb air pollution, provide shade, and beautify the school environment. The results of the activity show an increase in environmental awareness among students and teachers, as well as the creation of a green area that functions as an outdoor learning space supporting interactive environmental education. This activity is expected to have a long-term positive impact on the quality of the school environment and to shape a generation of youth that is concerned about environmental preservation.